2001
DOI: 10.1023/a:1010687017717
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacokinetic-Pharmacodynamic Relationships for Docetaxel

Abstract: The population approach has been implemented prospectively in the clinical development of docetaxel (Taxotere). Overall 640 patients were evaluable for the population PK/PD analysis. The PK analysis evidenced significant covariates explaining the inter-patient variability of docetaxel clearance and the PK/PD analysis demonstrated that the variability in clearance was a significant predictor of several safety endpoints. In patients with clinical chemistry suggestive of mild to moderate liver function impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…Uptake experiments were performed with these agents in the presence or absence of rifampin as described. 39 …”
Section: Methodsmentioning
confidence: 99%
“…Uptake experiments were performed with these agents in the presence or absence of rifampin as described. 39 …”
Section: Methodsmentioning
confidence: 99%
“…Аналогичный эффект отмечен и при сочетании с дру-гими сильными ингибиторами CYP3A4, например с ке-токоназолом -снижение клиренса доцетаксела на 40-50 %. В то же время проведение пре-и постмедикации дексаметазоном не повлияло на фармакокинетику так-сана [51]. При этом безопасность комбинации кабази-таксела с данными препаратами не оценивалась, одна-ко с учетом схожего механизма действия есть основания предполагать и схожий результат.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…It has been reported that an average of 37% of obese patients undergoing bariatric surgery have NASH, which is higher than the rate observed in the general US adult population (Lazo and Clark, 2008). For both morphine and docetaxel, hepatic dysfunction is well documented to alter PK and requires dose-adjustment to avoid the occurrence of ADRs, potentially due to alteration in hepatic metabolism and transporter function (Bruno et al, 2001; Eckmann et al, 2014; Hasselström et al, 1990; Linares et al, 2009; Ozawa et al, 2008, 2009; Yoon et al, 2012). For docetaxel, several studies have attempted to assess whether doses should be adjusted based on various measures of obesity and body surface area (Griggs et al, 2012; Rudek et al, 2004; Sparreboom et al, 2007).…”
Section: Why Is Nash Currently Not Identified As a Key Player In Imentioning
confidence: 99%